The myeloid SRC family kinase HCK regulates breast cancer growth by activating tumor-associated macrophage-led invasion and inhibiting cytotoxic T cell activity - Murrey, Michael W.; Poh, Ashleigh R.; Steer, James H.; Rinaldi, Catherine; Mouchemore, Kellie A.; Dwyer, Amy R.; Denisenko, Elena; Kuznetsova, Irina; Yeow, Yen; Jones, Matthew E.; Hmon, Khaing P. W.; Muirí, Dáithí Ó; et al. (Frontiers in Immunology, 2026)
IntroductionThe normal developmental and homeostatic roles of tissue resident macrophages are subverted in tumor-associated macrophages to promote tumor progression. Pro-tumoral macrophage activities include immune suppression and promotion of invasion and metastasis. While the myeloid Src family kinase HCK is known to regulate immune evasion, here we show that HCK promotes growth of an aggressively invasive mammary tumor through activation of macrophage motility and invasive capacity.MethodWe used the Py8119 mouse mammary tumor model to investigate the role of Hck activity in tumor growth through therapeutic inhibition and genetic modification. Single cell RNA sequencing and immunohistochemistry approaches were used to investigate changes to the immune compartment.ResultsLoss of HCK activity reduced the growth of Py8119 mammary tumors by 70-80% while excessive HCK activity increased growth four-fold. Consistent with a role for HCK in macrophage invasiveness, plasma membrane-associated Src family kinase activity at the tumor margins was lost in the absence of HCK. Regarding immune evasion, HCK-deficient tumors contained increased CD8+ T cell numbers and, while CD8+ T cell depletion reduced survival in all mouse cohorts, CD8+ T cell-depleted HCK-deficient mice survived much longer than CD8+ T cell-replete control mice. Characterisation of the tumour microenvironment by single cell sequencing showed 5 major subtypes of TAMs (immunoregulatory (Folr2high ), inflammatory (MHC-IIhigh ), interferon-primed, angiogenic and tissue resident), which together made up 40% of cells in the tumour. While Hck activity did not affect the recruitment of TAMs or their subtype composition, pathway analysis showed that its loss decreased TAM motility and increased their interferon signalling and reduced EMT pathways in the Py8119 tumor cells.ConclusionThis study provides evidence that HCK activity in TAMs enhances tumour growth via promotion of invasive behaviour as well as suppression of anti-tumor immunity. These findings highlight HCK as a promising therapeutic target to limit tumor progression.